2021
DOI: 10.3389/fpubh.2021.660600
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Demographic Variables Influencing Dementia Literacy and Risk Perception Through a Global Survey

Abstract: Dementia literacy is important for risk mitigation and preventative strategies before disease onset. The aim of our study was to investigate dementia literacy and how demographic characteristics influence these perceptions in order to provide evidence for how dementia-centered public health initiatives should structure their focus. We conducted a globally administered online survey, through Amazon Mechanical Turk (mTurk). Survey items evaluated: (1) personal perception on the preventability of dementia, and (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…In contrast to prior research, our study found minimal associations between sociodemographic characteristics and dementia literacy. Previous studies report that individuals who are male, have low levels of education, and are older, are less aware of the possibility of dementia risk reduction [34,48] and have poorer knowledge regarding the prevalence, symptoms, and treatment of dementia [30]. This discrepancy may be explained through a comparison of the sociodemographic features between the present sample and those in prior research.…”
Section: Dementia Literacycontrasting
confidence: 55%
“…In contrast to prior research, our study found minimal associations between sociodemographic characteristics and dementia literacy. Previous studies report that individuals who are male, have low levels of education, and are older, are less aware of the possibility of dementia risk reduction [34,48] and have poorer knowledge regarding the prevalence, symptoms, and treatment of dementia [30]. This discrepancy may be explained through a comparison of the sociodemographic features between the present sample and those in prior research.…”
Section: Dementia Literacycontrasting
confidence: 55%
“…The information that was most frequently shared in this study related to factors that are more widely believed to influence dementia risk such as diet, physical activity and cognitive activity, rather than risk factors with stronger empirical support 3,5,8,29 . It has been suggested that information is more likely to be shared if it is emotionally provocative, practically useful, interesting and surprising 30 .…”
Section: Discussionmentioning
confidence: 81%
“…The information that was most frequently shared in this study related to factors that are more widely believed to influence dementia risk such as diet, physical activity and cognitive activity, rather than risk factors with stronger empirical support. 3,5,8,29 It has been suggested that information is more likely to be shared if it is emotionally provocative, practically useful, interesting and surprising. 30 It has also been suggested that information diffuses most readily through a community if it is perceived as being advantageous, compatible with previous practices and beliefs (familiar) and easy to understand and implement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation